A new species of Hyphessobrycon (Characiformes, Characidae) from the Esteros del Iberá wetlands, Argentina - Almirón, Adriana Edith (2004)
Hyphessobrycon auca sp. n. is described from the Esteros del Iberá wetlands. Hyphessobrycon auca differs from the remaining species of the genus by the presence of one maxillary tooth with 5 cusps; dentary low with teeth decreasing in size anteroposteriorly; males with hooks in all fins; mature females with hooks on pelvic-fin rays; one humeral spot vertically elongated, bounded by a light area; a second lateral spot may be faint or well developed; a wide lateral band ending in a conspicuous caudal spot.